APPLICATION DESIGN USE OF THE LANGKAT COMMAND CENTER HALL - Syahputra, Ardianta; Khair, Fikri; Syukri, Khairiadi; Mansis, M. Zikri Ilham; Abiyu, Nadhif; Kurniawan, Fahmi (Cattleya Darmaya Fortuna, 2025)
In today's world of digitalization, many government and private agencies have implemented it, this is a form of manifestation of following the development of technology that follows the times so that the agency is not outdated. Langkat communication and informatics office has a langkat command center hall that can be used for agencies in the langkat district that will conduct activities. However, the system for submitting usage is still offline, namely by using paper media as an intermediary for communication in submitting requests for use. Of course, things like this have several obstacles, namely the slow approval process and sometimes the application letter data is not well served. In this era of information technology, of course, the Department needs an application that can help to process data on the use of the Langkat Command Center Hall using digitalized media. Therefore, in this study built an application for the use of Aula Langkat Command Center. With the aim that it can help the department to manage the data use of the hall effectively, efficiently and can improve the quality of service and reduce processing time and minimize errors.